Principles of politics : a rational choice theory guide to politics and social justice - Oppenheimer, Joe. (New York, 2012)
Principles of Politics: A Rational Choice Theory Guide to Politics and Social Justice Modern rational choice and social justice theories allowscholars to develop new understandings of the foundations andgeneral patterns of politics and political behavior. In this book,Joe Oppenheimer enumerates and justifies the empirical and moralgeneralizations commonly derived from these theories. In developingthese arguments, Oppenheimer gives students a foundational basis ofboth formal theory and theories of social justice, and theirrelated experimental literatures. He uses empirical findings toevaluate the validity of the claims. This basic survey of thefindings of public choice theory for political scientists coversthe problems of collective action, institutional structures,citizen well-being and social welfare, regime change and politicalleadership. Principles of Politics highlights what is universal toall of politics and examines both the empirical problems ofpolitical behavior and the normative conundrums of socialjustice. Contents Introduction: politics, universals, knowledge claims, andmethods Part I. The Logic of Collective Action: 1. Voluntary contributions and collective action 2. Going beyond the prisoner dilemma 3. Collective action applications to and beyond democraticpolitics Part II. Collective Choice: 4. Individual to collective choice in one dimensionalpolitics 5. Individual to collective choice more generally Part III. Political Institutions and Quality Outcomes: 6. Political necessity and the tethering of leaders 7. A few institutional pitfalls Part IV. Social Justice, Choice, and Welfare: 8. The general problem of collective welfare and choice 9. Voting rules 10. Social welfare and social justice: a partial integration Conclusion: 11. Questions and lessons.
Keywords: "Political science, Rational choice theory, Social justic"